(untitled) (Medico Legal Update, 2021)
Central Sulawesi in 2018 showed the number of outpatient visits as much as 71.8%. The number of outpatient visits to First Level Health Facilities with the highest percentage was Palu City with 711,394 cases. The number of participants of the National Health Insurance in 2019 in Palu City was 476,968 thousand. The highest number of referrals in 13 public health centers in Palu City in 2019, namely the Birobulipublic health center with the highest number of per quarter I 1384 and in the second quarter as many as 1172 cases. Type of Research is a qualitative case study approach. The research informants were 7 informants. The results showed that the communication variable between the implementers was quite good in implementing the referral system but sometimes it was not consistent, there were no meetings or meetings to discuss reference standards or referral issues. In terms of infrastructure, resources are good, there is still a lack of medical personnel, there is no training regarding referral standards. The Implementers’ attitude/disposition and knowledge of medical personnel about the referral system are good. Standard Operational Procedures already exist but have not been socialized in every public health center.